Multi-scale experiments on soft body armors under projectile normal impact. (October 2017) - Chen, W.; Hudspeth, M.; Guo, Z.; Lim, B.H.; Horner, S.; Zheng, J.Q.
Highlights: This article summarizes the recent experimental research at Purdue University on the transverse impact response and failure of soft body armors at scales from a single fiber to a yearn to single-ply fabric to pack level in an integrated way. Abstract: Soft body armors have been widely used by law-enforcement and military personnel. However, predictive capabilities on the critical conditions for the impact failure of these armors are still not well-developed. As part of a special issue, this article summarizes our recent experimental research efforts aiming at developing a better understanding of impact failure of soft body armors at several size scales, ranging from shoot packs, single-plies, yarns, and fibers. The experiments reveal that impact resistance of packets is dictated by axial properties and shear strength of the textile materials, as well as structural properties such as weave patterns. At the single-ply level, the critical impact velocity depends heavily on the nose shape of the projectiles, as well as the axial and transverse properties of the yarns. The failure of yarns and fibers depends on the stress state, as interpreted from the effects of nose shapes of the indenters and from the application of multi-axial stress states. The effects of aging on the impact resistance is also discussed.